2001
DOI: 10.1007/s004240000485
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the protein-kinase-A-dependent regulation of CFTR Cl - channels and Na + -K + pumps in guinea-pig ventricular myocytes

Abstract: Protein-kinase-A- (PKA-) dependent regulation of cystic fibrosis transmembrane conductance regulator (CFTR) Cl- current (I(CFTR)) and Na+-K+ pump current (Ip) was studied in single guinea-pig ventricular myocytes. Both currents were measured simultaneously by means of whole-cell recording at 30 degrees C. The adenylyl cyclase activator forskolin was used to stimulate PKA activity. At -20 mV, forskolin (4 microM) induced a fast activation of I(CFTR) and a delayed stimulation of Ip. Despite the strikingly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…ϩ -K ϩ pump inhibition mediated by cAMP-dependent pathways in cardiac myocytes was reported in early studies (8,9), but many more recent studies have reported that these pathways mediate pump stimulation either by increasing maximal pump rate or by increasing pump affinity for intracellular Na ϩ (7,(11)(12)(13)(14)(15)(16)30). In our study, forskolin induced glutathionylation of the Na ϩ -K ϩ pump ␤ 1 subunit.…”
Section: Nasupporting
confidence: 53%
See 1 more Smart Citation
“…ϩ -K ϩ pump inhibition mediated by cAMP-dependent pathways in cardiac myocytes was reported in early studies (8,9), but many more recent studies have reported that these pathways mediate pump stimulation either by increasing maximal pump rate or by increasing pump affinity for intracellular Na ϩ (7,(11)(12)(13)(14)(15)(16)30). In our study, forskolin induced glutathionylation of the Na ϩ -K ϩ pump ␤ 1 subunit.…”
Section: Nasupporting
confidence: 53%
“…We have found the ␤ 3 adrenergic receptor mediates stimulation of the Na ϩ -K ϩ pump in cardiac myocytes (5). 5 We, therefore, used forskolin, as have most of the recent studies (7,11,12,15,16).…”
Section: Namentioning
confidence: 99%
“…CFTR is a widely expressed transport protein and has been found outside the lung in sweat glands, uterine cervix, vas deferens, intestine, liver, pancreas, immune cells and heart (Davis et al, 1996;Kockskämper et al, 2001). CFTR is a member of the ABC transporter proteins and is involved in the regulation of the transport of monovalent ions, acetylcholine representing a monovalent permanent ion.…”
Section: Discussionmentioning
confidence: 99%
“…CFTR is a widely expressed transport protein and has been found outside the lung in sweat glands, uterine cervix, vas deferens, intestine, liver, pancreas, immune cells and heart (Davis et al, 1996;Kockskämper et al, 2001). Previously it has been shown that the content of acetylcholine is reduced in isolated airways and peripheral leucocytes obtained from CF-patients and first evidence for a co-localization of choline-acetyltransferase (ChAT) and CFTR was found in human mononuclear cells .…”
Section: Discussionmentioning
confidence: 98%